Development Of An E-Module Using The Book Creator Application For Teaching Various Cuts Of Animal-Based Food Ingredients To Phase E Culinary Vocational School Students - Saraswati, Yurin; Handajani, Sri; Purwidiani, Niken; Lukitasari, Febri (Universitas Negeri Padang, 2025)
This study aimed to develop an E-module using the Book Creator application on the topic of various cuts of animal-based food ingredients. The study also aimed to determine the feasibility of the material content and media design, and to analyze students' responses to the developed E-module. This research employed the 4D development model proposed by Thiagarajan, which consists of four stages: Define, Design, Development, and Dissemination. This study was limited to the Development stage due to time constraints. Data were collected through expert validation and student response questionnaires. The feasibility of the E-module was evaluated by three material experts and three media experts. The research was conducted with 32 Phase E (Grade X) culinary students at SMK Negeri 3 Kediri, Indonesia. The quantitative data obtained from validation sheets and student response questionnaires were analyzed using descriptive quantitative analysis by calculating the percentage score of each assessment aspect and interpreting the results based on predetermined feasibility criteria. Qualitative data in the form of suggestions and comments from validators were analyzed descriptively to support the quantitative findings. The results showed that: (1) the developed E-module on various cuts of animal-based food ingredients was published in the form of an online link (https://bit.ly/readbookcreator); (2) the material feasibility achieved an average score of 90%, categorized as very feasible, while the media feasibility achieved an average score of 92%, also categorized as very feasible; and (3) students' responses obtained an average score of 83%, categorized as very feasible. In conclusion, the E-module developed using the Book Creator application is highly feasible and suitable for use in the learning process. Further research is needed to examine the effectiveness of this E-module on students' practical learning outcomes in animal-based food carcass cutting techniques.